Dysphagia progression and swallowing management in Parkinson's disease: an observational study - Karen Fontes Luchesi; Satoshi Kitamura; Lucia Figueiredo Mourão (Brazilian Journal of Otorhinolaryngology, 2015)
Introduction: Dysphagia is relatively common in individuals with neurological disorders. Objective: To describe the swallowing management and investigate associated factors with swallowing in a case series of patients with Parkinson's disease. Methods: It is a long-term study with 24 patients. The patients were observed in a five-year period (2006-2011). They underwent Fiberoptic Endoscopic Evaluation of Swallowing, Functional Oral Intake Scale and therapeutic intervention every three months. In the therapeutic intervention they received orientation about exercises to improve swallowing. The Chi-square, Kruskal-Wallis and Fisher's tests were used. The period of time for improvement or worsening of swallowing was described by Kaplan-Meier analysis. Results: During the follow-up, ten patients improved, five stayed the same and nine worsened their swallowing functionality. The median time for improvement was ten months. Prior to the worsening there was a median time of 33 months of follow-up. There was no associated factor with improvement or worsening of swallowing. The maneuvers frequently indicated in therapeutic intervention were: chin-tuck, bolus consistency, bolus effect, strengthening-tongue, multiple swallows and vocal exercises. Conclusion: The swallowing management was characterized by swallowing assessment every three months with indication of compensatory and rehabilitation maneuvers, aiming to maintain the oral feeding without risks. There was no associated factor with swallowing functionality in this case series.